Spectrophotometric Determination of Chloramphenicol in Pharmaceutical Preparations - Tamathir A. Hamoudi; Wadala A. Bashir (College of Education for Pure Sciences, 2018)
A spectrophotometric method for the determination of trace amounts of chloramphenicol has been proposed. This method depends upon the reduction of the nitro to amino group, condensation with promethazine reagent in the presence of cerium (IV) ions to form a colored dye which exhibits maximum absorption at 606 nm with a high sensitivity (molar absorptivity is 1.292×104 l.mol-1.cm-1, and Sandell's sensitivity index of 0.025 μg/cm2). Beer' s law is applied within the concentration range of obeyed in 0.4 to 12 ppm with a relative error of -2.73 to + 0.37% and a relative standard deviation of ± 3.84 to ± 0.44%, depending on the concentration level. The method has been successfully applied to the determination of chloramphenicol in pharmaceutical preparations (capsules, eye drop and eye ointment).